Sewage sludge coke estimation using thermal analysis - Viana, Marcelo Mendes [UNESP]; Maltez Melchert, Maura Berger [UNESP]; de Morais, Leandro Cardoso [UNESP]; Buchler, Pedro Mauricio [UNESP]; Dweck, Jo (Springer, 2011)
The imposition of more stringent legislation by CETESB in the State of So Paulo (Brazil) governing the disposal and utilization of sewage sludge, coupled with the growth in its generation has prompted a drive for alternative uses of sewage sludge. One option that is especially promising, due to its potential to valorize sludge, is its conversion into carbonaceous adsorbents or coke for industrial effluents treatment. Thus, a methodology is presented to estimate the coke produced from the sludge of a sewage treatment station using thermal analysis. The used sewage sludge, which comes from aerobic treatment, was collected in the wastewater treatment station of Barueri, one of the largest of the So Paulo metropolitan area. The sludge samples were collected, dried, ground, and milled until they passed an ABNT 200 sieve. The inert ambient used during its thermal treatment produces inorganic matter and coke as residual materials. Coke formation occurs in the 200-500 A degrees C range and, between 500 and 900 A degrees C, its thermal decomposition occurs. The highest formation of coke occurs at 500 A degrees C.
Keywords: Sewage sludge; Coke; TG; Thermal decomposition